2013
DOI: 10.1507/endocrj.ej12-0290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additional administration of acarbose on blood glucose fluctuations and postprandial hyperglycemia in patients with type 2 diabetes mellitus under treatment with alogliptin

Abstract: Abstract. Acarbose was administered at 300 mg/day to patients with type 2 diabetes mellitus (T2DM) who had been taking 25 mg/day of alogliptin, and levels of blood glucose were analyzed by continuous glucose monitoring (CGM) for 3 days. The mean blood glucose level with acarbose (136.4 ± 30.7 mg/dL) did not differ significantly from that without acarbose (141.7 ± 28.3 mg/dL). However, in the condition of the combination therapy, there were significant decreases in the standard deviation of the mean blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…As a result, GV is regarded as an important risk factor in the development of diabetic complications. Our results confirmed previously published papers reporting that acarbose reduced GV [3][4]11]. Saxagliptin is a dipeptidylpeptidase-4 (DPP-4) inhibitor, which increase glucose-dependent insulin secretion and suppress glucagons secretion [12].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As a result, GV is regarded as an important risk factor in the development of diabetic complications. Our results confirmed previously published papers reporting that acarbose reduced GV [3][4]11]. Saxagliptin is a dipeptidylpeptidase-4 (DPP-4) inhibitor, which increase glucose-dependent insulin secretion and suppress glucagons secretion [12].…”
Section: Resultssupporting
confidence: 91%
“…It should be considered along with HbA1c in the management of diabetes [2]. As an add-on drug, acarbose is known to improve GV [3][4].Saxagliptin is a new anti-diabetic drug, whose effect on GV is still unclear. Therefore we compared the glucose control and GV between saxagliptin and acarbose as add-on therapies for aged type 2 diabetes mellitus (T2DM) inadequately controlled with metformin alone.…”
Section: Introductionmentioning
confidence: 99%
“…For detailed clinical pharmacology of alogliptin, please read recent reviews about this drug. 38,[41][42][43][44][45][46][47][48][49] Alogliptin as monotherapy or added to metformin, [50][51][52] pioglitazone, [53][54][55][56] glipizide, 57,58 glyburide/glibenclamide, 59 voglibose, [60][61][62] miglitol, 62 acarbose, 63 or insulin 64,65 significantly improves glycaemic control compared with placebo or active comparators in adult or elderly patients with inadequately controlled T2DM. This is associated with good gastrointestinal tolerability and a low incidence of hypoglycaemia.…”
Section: Dpp-4 Inhibitors In Diabetes Treatmentmentioning
confidence: 99%
“…Second, the combined use of alogliptin might favorably modulate the glucose-lowering effect of voglibose, via enhancing its effect on incretin, especially glucagon-like peptide 1 (GLP-1) [30,31,43,44]. Alpha-glucosidase inhibitors prolong and enhance the secretion of GLP-1 from the intestine [45][46][47][48][49][50], whereas DPP-4 inhibitors suppress the inactivation of the secreted incretin.…”
Section: Association Of Clinical Parameters With the Response To Voglmentioning
confidence: 99%
“…Recently, a favorable effect of alpha-glucosidase inhibitors as an add-on to DPP-4 inhibitors has been suggested by some clinical studies [30][31][32]. In addition, it is also suggested that although the agents are usually administered thrice a day, only a once-daily administration might have some efficacy on glycemic control [33].…”
mentioning
confidence: 99%